EXTRACTION OF PECTIN FROM THE ROOM OF HELIANTHUS TUBEROSUS L. (TOPINAMBUR) IN DIFFERENT MEDIA AND DETERMINATION OF FUNCTIONAL GROUPS (Scientific journal of the Fergana State University, 2023)
This article identifies the proteins, pectin, amino acids, organic and fatty acids in Jerusalem artichoke root. The physicochemical properties of the isolated pectin samples were studied by titrometric, viscometric, and other methods. However, the relative purity of pectin isolated in a strongly acidic medium with an uronid content of 85% of the pectin substance was experimentally described.